Menstruation as a Weapon of War: The Politics of the Bleeding Body for Women on Political Protest at Armagh Prison, Northern Ireland - Wahidin, Azrini (The prison journal, 2019)
This article draws on the voices of women political prisoners who were detained at Armagh Prison during the period of the Troubles or the Conflict in Northern Ireland. It focuses on women who undertook an extraordinary form of protest against the prison authorities during the 1980s, known as the No Wash Protest. As the prisoners were prevented from leaving their cells by prison officer either to wash or to use the toilet, the women, living in the midst of their own dirt and body waste, added menstrual blood as a form of protest.